Chemithermomechanical Pulping and Properties Comparison of Four Common Hardwood Species in Northern China - Chuanmin Geng; Chuanyuan Yang; Zhenli Xu; Lianchen Xu; Yuquan Zhang; Yingjuan Fu; Guoyu Tian; Zhaojiang Wang (BioResources)
Populus cathayana Rehder (PCR, Chinese poplar), Fraxinus chinensis Roxb. (FCR, Chinese ash), Platanus orientalis L. (PO, Oriental plane), and Acer palmatum Thunb. (AP, Japanese maple) are four common hardwoods in the northern hemisphere. In this work, chemithermomechanical pulps (CTMP) of the four wood species were prepared for comparative study of pulp properties. For unbleached CTMP, PCR and FCR exhibited the highest whiteness of 44%ISO, while AP demonstrated the highest tensile index of 24.2 N·m²/g, tear index of 1.23 mN·m2/g, and ring crush index of 7.2 N·m/g. For bleached CTMP using hydrogen peroxide, PO achieved the highest whiteness of 70.3% ISO at 6% hydrogen peroxide. AP showed the optimal tensile index of 24.7 N·m²/g. The experiments also revealed that PO exhibited the highest bulk of 3.6 cm³/g. This study provides a reference for selecting raw materials in pulp production.